2009
DOI: 10.1091/mbc.e08-06-0621
|View full text |Cite
|
Sign up to set email alerts
|

A Shared Mechanism of Adhesion Modulation for Tenascin-C and Fibulin-1

Abstract: Adhesion modulatory proteins are important effectors of cell-matrix interactions during tissue remodeling and regeneration. They comprise a diverse group of matricellular proteins that confer antiadhesive properties to the extracellular matrix (ECM). We compared the inhibitory effects of two adhesion modulatory proteins, fibulin-1 and tenascin-C, both of which bind to the C-terminal heparin-binding (HepII) domain of fibronectin (FN) but are structurally distinct. Here, we report that, like tenascin-C, fibulin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Consistent with its distribution at the edges of the wounds, tenascin-C may promote migration rather than premature contraction (Midwood et al 2004). A similar mechanism of adhesion modulation has been proposed for the unrelated protein, fibulin-1, suggesting that this may be a common mechanism to fine-tune adhesion (Williams and Schwarzbauer 2009). Other research, again in fibroblasts, has shown that the blocking of fibronectin-syndecan-4 interaction by tenascin-C inhibits cell anchorage on fibronectin, leading to the blockage of cell cycle progression but the stimulation of tumour cell proliferation (Orend et al 2003;, Huang et al 2001).…”
Section: Tenascin-cmentioning
confidence: 61%
“…Consistent with its distribution at the edges of the wounds, tenascin-C may promote migration rather than premature contraction (Midwood et al 2004). A similar mechanism of adhesion modulation has been proposed for the unrelated protein, fibulin-1, suggesting that this may be a common mechanism to fine-tune adhesion (Williams and Schwarzbauer 2009). Other research, again in fibroblasts, has shown that the blocking of fibronectin-syndecan-4 interaction by tenascin-C inhibits cell anchorage on fibronectin, leading to the blockage of cell cycle progression but the stimulation of tumour cell proliferation (Orend et al 2003;, Huang et al 2001).…”
Section: Tenascin-cmentioning
confidence: 61%
“…N ϭ 5 for each condition; *P Ͻ 0.05. Third, TNC is known to restrain RhoA-mediated activation of the extracellular regulated kinase (Erk) pathway in fibroblasts (49), and it has recently been shown that Erk signaling opposes Smad-dependent TGF-␤ signaling in lung epithelial cell lines, potentially regulating both epithelial-mesenchymal and mesenchymal-epithelial transitions (39). While speculative, it is possible that the absence of TNC after ALI leads to excessive Erk signaling which may in turn reduce Smad-3 through effects on transcription and proteasomal activity by as yet undescribed mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research by Selwyn et al showed that fibulin-1 can alter ECM-mediated cell signaling through inhibiting ERK activation. 35 Collectively, these findings provide evidence that fibulin-1 plays a crucial role in neuronal apoptosis after SCI by blocking ERK signaling pathways in neurons. Consideration of other known ligands of fibulin-1 leads us to propose that fibulin-1-mediated apoptosis may also occur through additional signaling pathways.…”
Section: Discussionmentioning
confidence: 80%